1999
DOI: 10.1677/erc.0.0060235
|View full text |Cite
|
Sign up to set email alerts
|

The potential of aromatase inhibitors in breast cancer prevention.

Abstract: Substantial evidence supports the concept that estrogens cause breast cancer in animals and in women but the precise mechanism is unknown. The most commonly held theory is that estrogens stimulate proliferation of breast cells and thus statistically increase the chances for genetic mutations which could result in cancer. Another theory is that estrogen metabolism generates oxygen-free radicals and quinones which produce both stable and unstable DNA adducts. Both result in genetic mutations which accumulate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…6 Tsutsui et al 10 demonstrated that catechol estrogens have various genotoxic effects, such as chromosomal aberrations and gene mutations. Taken together with the previous and present results, it is concluded that in estrogen-induced carcinogenesis, estrogen metabolites, particularly catechol estrogens, are involved in the initiation process through oxidative DNA damage and estrogens themselves enhance cell proliferation, leading to tumor promotion and/or progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Tsutsui et al 10 demonstrated that catechol estrogens have various genotoxic effects, such as chromosomal aberrations and gene mutations. Taken together with the previous and present results, it is concluded that in estrogen-induced carcinogenesis, estrogen metabolites, particularly catechol estrogens, are involved in the initiation process through oxidative DNA damage and estrogens themselves enhance cell proliferation, leading to tumor promotion and/or progression.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Estrogens can cause cancer by stimulating cell proliferation and causing genotoxic damage. 6,7 Estrogens are highly mitogenic in hormone-sensitive tissues, such as the uterus and breast. 8 Prolonged exposure of target tissues and cells to excessive mitogenic stimulation by estrogens has been considered an important etiological factor for the induction of estrogen-associated cancers in experimental animals and humans.…”
mentioning
confidence: 99%
“…Exemestane gives responses in patients with visceral disease who have failed antiestrogens (16). The intratumoral aromatase inactivator effects of exemestane are suggested to be potentially more significant than the estrogen lowering effects (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The only concern with these agents are the effects of estrogen depletion in target organs, such as the cardiovascular system and bones. This, perhaps, could be overcome by considering lower doses of highly potent agents, such as letrozole, which might inhibit local estrogen synthesis in the breast without decreasing ovarian estrogen production (Santen et al 1999).…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%